Study the Optical Properties of Fluorescein Sodium Dye Doped in Polymer Polyvinyl Alcohol - Khawla J. Tahir (Journal of Global Pharma Technology, 2018)
In this research, the linear and non-linear optical properties for laser dye fluorescein sodium in solvent Ethanol doped with polymer polyvinyl alcohol (PVA) at different concentrations (1x10-4,5x10-4,1x10-3,5x10-3,1×10-2,5x10-2) M were studied. Z-scan technique was used to determine the nonlinear optical properties like the refractive index (n2) and the absorption coefficient (β) at wavelength 532nm CW frequency doubling Nd-YAG laser. The results showing the nonlinear absorption coefficient (β) changes between saturated absorption and two-photon absorption of certain concentration while the refractive non-linear coefficient (n2) of film samples changes between positive (self-focusing) and negative (self-defocusing). The quantum efficiency has been calculated for the same above concentrations (87%, 83%, 76%, 73%, 70%, 67%) respectively.Keywords: Linear and non-linear optical properties, Fluorescein Sodium dye, Z-scan technique, fluorescence quantum efficiency.